Microbial community structure and shift pattern of industry brine after a long-term static storage in closed tank - Tu, Demei; Ke, Juntao; Luo, Yuqing; Hong, Tao; Sun, Siqi; Han, Jing; Chen, Shaoxing (Frontiers in Microbiology, 2022)
Brine from Dingyuan Salt Mine (Anhui, China), an athalassohaline hypersaline environment formed in the early tertiary Oligocene, is used to produce table salt for hundreds of millions of people. However, halophiles preserved in this niche during deposition are still unknown. Here, we employed cultivation and high-throughput sequencing strategies to uncover the microbial community and its shift after a long-term storage in the brine collected from Dingyuan Salt Mine. High-throughput sequencing showed 1) in the fresh brine (2021), Cyanobium_PCC-6307 spp. (8.46%), Aeromonas spp. (6.91%) and Pseudomonas spp. (4.71%) are the dominant species in bacteria while Natronomonas spp. (18.89%), Halapricum spp. (13.73%) and Halomicrobium spp. (12.35%) in archaea; 2) after a 3-year-storage, Salinibacter spp. (30.01%) and Alcanivorax spp. (14.96%) surpassed Cyanobium_PCC-6307 spp. (8.46%) becoming the dominant species in bacteria; Natronomonas spp. are still the dominant species, while Halorientalis spp. (14.80%) outnumbered Halapricum spp. becoming the dominant species in archaea; 3) Alcanivorax spp. and Halorientalis spp. two hydrocarbons degrading microorganisms were enriched in the brine containing hydrocarbons. Cultivation using hypersaline nutrient medium (20% NaCl) combined with high-throughput 16S rRNA gene sequencing showed that 1) the biomass significantly increased while the species diversity sharply declined after a 3-year-storage; 2) Halorubrum spp. scarcely detected from the environment total DNA were flourishing after cultivation using AS-168 or NOM medium; 3) Twelve possible new species were revealed based on almost full-length 16S rRNA gene sequence similarity search. This study generally uncovered the microbial community and the dominant halophiles in this inland athalassohaline salt mine, and provided a new insight on the shift pattern of dominant halophiles during a long-term storage, which illustrated the shaping of microorganisms in the unique environment, and the adaptation of microbe to the specific environment.